2014
DOI: 10.1002/2013jb010156
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in the Coulomb failure function on inland active faults in southwest Japan due to east‐west compression and interplate earthquakes

Abstract: Inland earthquake activity in and around the Kinki region, southwest Japan, increases in the period from several decades before to about a decade after the occurrence of great interplate earthquakes along the Nankai Trough. To quantitatively investigate this relationship, we calculated long-term changes in the Coulomb failure function (ΔCFF) on inland active faults in this region with viscoelastic slip response functions. As sources for the change in CFF, we investigated east-west compression within the Niigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…In fact, the seismicity in Wakayama showed significant quiescence after the 1944 Tonankai earthquake (e.g., Kanamori, ; Yoshioka & Hashimoto, ). Past studies reported that the seismic activation and quiescence in the inland area were associated with Nankai Trough earthquakes (e.g., Ogata, ; Shikakura et al, ). The stress fluctuation caused by the interplate locking and the huge Nankai Trough earthquakes significantly affects the occurrence time of the inland earthquakes.…”
Section: Activation/quiescence Of the Inland Seismicity Related To Humentioning
confidence: 99%
“…In fact, the seismicity in Wakayama showed significant quiescence after the 1944 Tonankai earthquake (e.g., Kanamori, ; Yoshioka & Hashimoto, ). Past studies reported that the seismic activation and quiescence in the inland area were associated with Nankai Trough earthquakes (e.g., Ogata, ; Shikakura et al, ). The stress fluctuation caused by the interplate locking and the huge Nankai Trough earthquakes significantly affects the occurrence time of the inland earthquakes.…”
Section: Activation/quiescence Of the Inland Seismicity Related To Humentioning
confidence: 99%
“…Mitogawa and Nishimura (2020) showed that a model incorporating the viscoelasticity successfully reproduces the activation of shallow inland earthquakes, not only before but also after the interplate earthquakes. Under a more realistic model setting, Shikakura et al (2014) explained this feature by computing the long-term viscoelastic Coulomb stress change on inland earthquake faults. They incorporated all possible deformation sources: the E-W compression observed as the Niigata-Kobe Tectonic Zone (Sagiya et al 2000), historical…”
Section: Discussionmentioning
confidence: 99%
“…Regarding an additional loading stress of the Awaji Island earthquake, we evaluated the Coulomb stress change (∆CFF) and its evolution after the Kobe earthquake, following the approach from Ohtani and Imanishi (2019). We assumed a one-dimensional viscoelastic structure used in Shikakura et al (2014), in which the thickness of the elastic layer is 35 km and the Maxwell viscosity of the viscoelastic layer is 5.0×10 18 Pa s. For the fault slip of the Kobe earthquake, we used a finite fault source model derived from the inversion of the near-source strong motion data (Ide and Takeo 1997). Most of the slip exists beneath Awaji Island, which is a feature commonly found in other slip models (Wald 1996;Koketsu et al 1998;Sekiguchi et al 2000).…”
Section: Stress Transferred By 1995 M W 69 Kobe Earthquakementioning
confidence: 99%
“…Regarding an additional loading stress of the Awaji Island earthquake, we evaluated the Coulomb stress change () and its evolution after the Kobe earthquake, following the approach from Ohtani and Imanishi (2019). We assumed a one-dimensional viscoelastic structure used in Shikakura et al (2014), in which the thickness of the elastic layer is 35 km and the Maxwell viscosity of the viscoelastic layer is 5.0×10 18 Pa s. For the fault slip of the Kobe earthquake, we used a nite fault source model derived from the inversion of the near-source strong motion data (Ide and Takeo 1997). Most of the slip exists beneath Awaji Island, which is a feature commonly found in other slip models (Wald 1996;Koketsu et al 1998;Sekiguchi et al 2000).…”
Section: Stress Transferred By 1995 Mw69 Kobe Earthquakementioning
confidence: 99%